Action of the Metalloproteinases in Gonadal Remodeling during Sex Reversal in the Sequential Hermaphroditism of the Teleostei Fish Synbranchus marmoratus (Synbranchiformes: Synbranchidae) - Mazzoni, Talita Sarah (2018)
Teleostei present great plasticity regarding sex change. During sex reversal, the whole gonadincluding the germinal epithelium undergoes significant changes, remodeling, and neoformation.However, there is no information on the changes that occur within the interstitial compartment.Considering the lack of information, especially on the role played by metalloproteinases (MMPs)in fish gonadal remodeling, the aim of this study was to evaluate the action of MMPs on gonadsof sex reversed females of Synbranchus marmoratus, a fresh water protogynic diandric fish. Gonadswere processed for light microscopy and blood samples were used for the determination of plasmasex steroid levels. During sex reversal, degeneration of the ovaries occurred and were graduallyreplaced by the germinal tissue of the male. The action of the MMPs induces significant changesin the interstitial compartment, allowing the reorganization of germinal epithelium. Leydig cellsalso showed an important role in female to male reversion. The gonadal transition coincides withchanges in circulating sex steroid levels throughout sex reversion. The action of the MMPs, in thegonadal remodeling, especially on the basement membrane, is essential for the establishment of anew functional germinal epithelium.